2021
DOI: 10.1021/acsphotonics.1c00885
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photodetection in Metal Nanocluster/Graphene Heterojunctions

Abstract: The molecule-like metal nanoclusters gained wide attention from biomedical to energy applications in recent years owing to their discrete spectra. These atomically precise metal nanoclusters exhibit a significant band opening and consequently the possibility for strong light emission. Based upon previous reports on conventional semiconductors, the semiconducting nature of these nanoclusters combined with two-dimensional semimetals can have a huge impact on optoelectronic devices. The present work demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…A hybrid structure of glutathione stabilized Au Nano clusters has been developed with a maximum photocurrent generation of 4 μA by Y.F. Chen and his team [47b] …”
Section: Resultsmentioning
confidence: 99%
“…A hybrid structure of glutathione stabilized Au Nano clusters has been developed with a maximum photocurrent generation of 4 μA by Y.F. Chen and his team [47b] …”
Section: Resultsmentioning
confidence: 99%
“…The sub-nanometer-sized MNCs with highly discretized energy levels are continuing to receive tremendous research attention as a fascinating class of functional materials owing to their sizedependent optical properties, excellent photo-stability, and promising bio-compatibility. [1][2][3][4] The highly tuneable optical properties of these ultra-small MNCs are the most demanding feature in multi-dimensional applications related to optoelectronics, [5][6] sensing, [7][8][9] light-harvesting, [10][11] and designing of luminescent light emitting devices. [12][13] Although the absolute origin of the PL properties of these MNCs is still obscure, the kernel-origin mechanism (due to the metallic core) and Ligand to Metal Charge Transfer (LMCT) mechanism (due to the ligand shell) are extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al have designed a highly sensitive photodetector fabricated with metal nanoclusters and a graphene heterojunction. It exhibited a high photoresponse due to the efficient separation and transportation of charge carriers through the heterojunction . Liu et al have demonstrated a broadband photodetector based on the SnO 2 /Si heterostructure with a spherical cavity-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibited a high photoresponse due to the efficient separation and transportation of charge carriers through the heterojunction. 7 Liu et al have demonstrated a broadband photodetector based on the SnO 2 /Si heterostructure with a spherical cavity-like structure. The large active surface area endows ultrafast photodetection ability with a very high detectivity value.…”
Section: ■ Introductionmentioning
confidence: 99%